Cancer Care Management – The Importance of An Interdisciplinary Model - Isabel Fernandes; Maria do Céu Rueff; Portela, S. (International Network of Business and Management Journals, 2013)
Healthcare costs are rising in oncology as new expensive drugs are developed each year. Nevertheless, cutting costs in healthcare is also a reality and a new evaluation of the problem is therefore needed. This essay analyzes the problem of prescription in Oncology in a Europe facing an economic crisis. Literature review, document analysis and interviews with key informants were all used for this purpose. A healthcare management reform in which the economic and financing issues are connected with the medical and ethical ones, centered in the patient, is proposed.